Anxiety experienced by individuals with cancer in remission. - Firmin, Michael W.; Pathammavong, Megan Bailey; Johnson, Courtney B.; Trudel, Janna Foster (Psychology, Health & Medicine, 2014)
For this qualitative research study, we interviewed 25 individuals who survived cancer regarding the sentiments they experienced in adjusting to having their condition in remission. Among other findings that we reported elsewhere, two themes emerged from the in-depth interviews relating to apprehensive percepts. One was that participants spoke of their tendency to battle worrisome thoughts. Although they used a variety of words in describing the construct, anxiety repeatedly appeared as a cogent emotion when facing cancer. Second, anniversaries were said to have continued cogence for the participants as they triggered memories and tended to generate degrees of anxiety.